No Strong Evidence of Priming Effects on the Degradation of Terrestrial Plant Detritus in Estuarine Sediments - Gontikaki, Evangelia; Witte, Ursula (Frontiers in Marine Science, 2019)
The occurrence of priming effects on the degradation of particulate terrestrial organic matter (13C-wheat detritus) was studied in marine sediments using phytoplankton detritus as priming inducer. Two scenarios, i.e. single-pulse vs. repetitive deposition of same amounts of algal detritus, were tested in sediment core incubation experiments. In the first case, a single pulse of phytodetritus simulated emulated the sudden large input of phytoplanktonic material onto sediments following the decline of spring blooms in surface waters, whereas the repetitive deposition of small amounts of algal detritus represented the low, continuous flow of marine input of either pelagic or benthic origin that remains significant all year round. The mineralization rate of wheat detritus to 13CO2 in each treatment was measured in sediment core incubations on days 6, 8, 14 and 20 following the initiation of the experiment. No evidence of priming effects on 13C-wheat mineralisation upon the addition of labile phytodetritus could be detected in either treatment scenario under the experimental conditions employed in this study in this study.